Light enhanced cognitive behavioral therapy for insomnia and fatigue during chemotherapy for breast cancer: a randomized controlled trial. Issue 3 (7th October 2021) - Bean, Helena R; Diggens, Justine; Ftanou, Maria; Alexander, Marliese; Stafford, Lesley; Bei, Bei; Francis, Prudence A; Wiley, Joshua F
Abstract: Study Objectives: Sleep problems are common during chemotherapy for breast cancer (BC). We evaluated whether combined brief cognitive behavioral and bright light therapy (CBT-I + Light) is superior to treatment as usual with relaxation audio (TAU+) for insomnia symptoms and sleep efficiency (primary outcomes). Methods: We randomized women receiving intravenous chemotherapy, stratified by tumor stage and insomnia severity index, to 6-week CBT-I + Light or TAU+. CBT-I + Light included 1 in-person session, 1 telephone call, 7 emails, and 20 min bright light (BL) each morning. TAU+ comprised usual treatment and two emails with relaxation audio tracks. Patient-reported outcomes were assessed at baseline, midpoint (week 3), post (week 6), and 3-month follow-up. Results: Women ( N = 101) were randomly assigned to CBT-I + Light or TAU+. The CBT-I + Light group showed significantly greater improvement in insomnia symptoms than the TAU+ group (−5.06 vs −1.93, p = .009; between-group effect size [ES] = .69). At 3-month follow-up, both groups were lower than baseline but did not differ from each other (between-group ES = .18, p = .56). CBT-I + Light had higher patient-reported sleep efficiency than TAU+ immediately after the start of intervention ( p = .05) and significantly greater improvement in fatigue (between-group ES = .59, p = .013) and daytime sleep-related impairment (between-group ES = .61, p = .009) than the TAU+ group. Conclusions: CBT-I + Light had a clinically significant impact on insomnia and fatigue with moderate ESs. Results support offering cognitive behavioral therapy for insomnia and BL therapy during chemotherapy for BC to help manage sleep and fatigue. Clinical Trial: Australian New Zealand Clinical Trials Registry (http://anzctr.org.au/ ). Registration number: ACTRN12618001255279.